Childhood as a structural form (Educação e Pesquisa, 2010)
In northern countries, a symbol of the consolidation of a knowledge area is the publication of a handbook - in Portuguese, manual or compendium - whose chapters give a state-of-the-art overview of their respective subjects. In 2009, The Palgrave Handbook of Childhood Studies was published as recognition of the area of childhood studies. It is known that children were mainly investigated by psychology or by pedagogy and that social sciences have produced little about them, giving priority to studies on the family or the school. Just over twenty years, however, children become the focus of social studies of childhood, as social phenomenon. In this sense, there is the field that investigates children as social agents, producing culture, and childhood as category in the social structure, which increased significantly the production of knowledge about the social relations established between the children themselves (their peers) and with adults (intra and intergenerational relations) on their skills as actors in their lives, as social agents whose actions modify / transform the social worlds in which they are inserted. The text of Professor Jens Qvortrup, responsible for the foundation of the first research group in sociology of childhood (RC53) at the International Sociological Association (ISA), and one of the organizers of the Handbook, focuses childhood as a social structure. Published as first chapter of The Palgrave Handbook of Childhood Studies, the study shows childhood as a segment in a social structure and the applications of a structural perspective, i.e. inserted in the theoretical studies of childhood, the chapter outlines an approach that differs from both research on socialization and studies on child development, providing evidence for the conduct of research that have as their object childhood as a social category, so diverse and complementary to other categories. The reading of the text directs to other important themes, presented by different authors in the other chapters of the Handbook, which makes Brazilian researchers expect the full translation of the book.